Der König kehrt zurück? Ein historischer Deutungsversuch der Alexanderinschrift aus Philippi (SEG 46, 787) - Bettermann, Niklas (Tekmeria, 2025)
The arbitration of a border dispute between the inhabitants of Philippi and Thracians by Alexander the Great (SEG 46, 787) is an exceptional, albeit controversial, historical document. A particularly influential interpretation by M. Hatzopoulos, based on substantial additions to the highly fragmentary text, dates the inscription to 330 BC and puts forward the hypothesis that the inscription provides unique evidence of Alexander’s intention to return after the conquest of Persepolis. While this thesis has stimulated considerable discussion, it has also faced justified but largely superficial criticism. The present article revisits the debate by offering a conservative edition of the inscription. The analysis provides a more nuanced interpretation of the textual basis and re-evaluates the date of the document, instead proposing a more plausible placement in late 335 BC. This revised dating facilitates broader historical contextualisation, particularly in relation to Alexander’s early consolidation of power in Greece—a topic that has received limited research attention thus far.